Software, Sovereignty and the Internet: Circumventing Chaos Through TRIPs - Bains, Manavinder Singh (Science and Technology Law Review, 2019)
This article explores the applicability, enforceability and logic of anti-circumvention provisions under international copyright law. The author suggests that digital copyrights should be enforced internationally via anti-circumvention measures prohibiting international trafficking in circumvention technologies under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs), which was put into effect by the World Trade Organization’s Multilateral Trade Negotiations in 1994. Since the adoption of this proposal could arguably limit international access to digital content, the article sets forth a proposal for exactly how TRIPs could be amended without limiting such access. Further, the article establishes an economic rationale for implementing the proposed amendment to TRIPs. The article also discusses how the proposed amendment might be implemented and the broad policy debate arising from its implementation.